IMPLEMENTASI KEBIJAKAN PENDIDIKAN GRATIS OLEH PEMERINTAH DAERAH KABUPATEN BADUNG SAAT PANDEMI COVID-19 (Jurnal Nawala Politika, 2022)
Education is a right for all people in Indonesia which makes the next government responsible for the implementation of free education in their respective regions. The emergence of the COVID- 19 pandemic and the enactment of the lockdown made the community's space to move very limited and had a very negative impact on economic conditions in Indonesia, especially for areas that depend on the tourism sector such as Badung Regency. This condition of course affects the implementation of policies in all sectors, including in terms of free education at the junior high school level which is the responsibility of the Badung Regency Government in carrying out its obligations to participate in the intellectual life of the nation. However, despite the pandemic situation, Badung Regency continues to implement the free education policy in its territory, despite all the limitations and changes that must be made to adapt. Keyword: Free Education, COVID-19 Pandemic, Badung Regency, Junior High School